2005
DOI: 10.1097/01.inf.0000188156.23182.eb
|View full text |Cite
|
Sign up to set email alerts
|

State of the Evidence for Standard-of-Care Treatments for Croup: Are We Where We Need to Be?

Abstract: Three conclusions were reached: (1) no steroid treatment studies of moderate or severe laryngotracheitis have been of adequate size to determine the risk of progressive viral infection or secondary bacterial infection; (2) single dose steroid treatment or limited nebulized use is probably safe; and (3) we should encourage better clinical diagnosis of croup illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Bacterial croup is usually secondary infection with Staphylococcus aureus, or other common bacterial pathogens like Streptococcus pyogenes, Streptococcus pneumoniae, Haemophilus influenzae or Moraxella catarrhalis [23]. It usually involves spreading of the infection and regarding pathology there is extensive exudate and pseudomembrane formation at the bronchial and bronchiolar levels, which results with progressive airway obstruction [23]. Over the decades there was a trend of antibiotic use, which was believed to prevent this obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacterial croup is usually secondary infection with Staphylococcus aureus, or other common bacterial pathogens like Streptococcus pyogenes, Streptococcus pneumoniae, Haemophilus influenzae or Moraxella catarrhalis [23]. It usually involves spreading of the infection and regarding pathology there is extensive exudate and pseudomembrane formation at the bronchial and bronchiolar levels, which results with progressive airway obstruction [23]. Over the decades there was a trend of antibiotic use, which was believed to prevent this obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies on recurrent croup and allergy showed that children with specific parainfluenza IgE antibodies who had croup more frequently released histamine into the airway than children with upper respiratory tract infection caused by the same pathogen [23,24]. The possible correlation between allergy and croup was investigated over the years, and this may have resulted in the usage of antihistaminics in treatment of croup [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations